Current Application of Chemometrics Analysis in Authentication of Natural Products: A Review - Rebiai, Abdelkrim; Hemmami, Hadia; Zeghoud, Soumeia; Ben Seghir, Bachir; Kouadri, Imane; Eddine, Laouini S.; Elboughdiri, Noureddine; Ghareba, Saad; Ghernaout, Djamel; Abbas, Nadir (Combinatorial Chemistry & High Throughput Screening, 2022)
Background: The efficiency of herbal medicinal products depends on the quantity of active ingredients in them, which can vary considerably in different contents. Hence, the quality control of herbal medicines is a critical concern. Objective: This paper aims to provide a succinct review of recent chemometrics applications in solving the uncertainty of the authentication of herbal medicines over the last two decades. Methods: Studies involving chemometrics applications in conjunction with various analytical methods have been categorized according to the type of research used in the quality evaluation of different samples, including chromatographic (HPLC, GC-MS) and spectroscopic analysis (UVVis, FTIR, NMR, and MS). Results: This review consists of over 90 studies illustrating the relevance of chemometrics methods in the discrimination based on the key bioactive components and phytochemical diversity of several herbs from closely related species. In addition to the prediction of the active components, the distinction between varieties and hybrids was accomplished through quantitative analysis techniques. Conclusion: Methods of chemometrics have provided an important and potent tool for the quality control and authentication of various herbs.
Keywords: quality control